Body Mass Index and Waist Circumferences Related to Uric Acid Level among Adults - Pramesti, Arindha Reni; Kusumaningati, Walliyana (Faculty of Medicine and Health Universitas Muhammadiyah Jakarta, 2020)
Background: the changes in metabolism in the body can trigger the increase of uric acid levels which can lead to a precursor of hyperuricemia and gout disease that can result extreme pain in the joint. Based on the study, it has known that uric acid levels can be caused by obesity, protein intake, lifestyle, and others. The anthropometric method which usually used to measured obesity are body mass index (BMI) and waist circumference (WC). Currently, the most commonly used ratio in this way is the Body Mass Index (BMI). Result: in a Canadian study among 151 adults, it was reported that there was a higher correlation between the area of abdominal visceral fat and WC compared with the correlation with the waist-hip circumference ratio. WC is also more strongly associated with total body fat, measured by densitometry, than by waist-to-hip circumference ratio. High levels of leptin in obese people can cause uric acid disruption through urine, so that uric acid levels in the blood of obese people become high. BMI also shows a positive relationship with leptin concentration, which is a trigger factor to increased uric acid levels. American adults also shown that uricemia related to their BMI value. Conclusion: BMI is one of the indicators of obesity, while obesity often thought to influence the incidence of gout by increasing uric acid levels in the blood. WC also closely related potentially to atherogenic metabolic disorders associated with abdominal obesity that to waist-to-hip circumference ratios.